PENGARUH PELAYANAN DAN PARTISIPASI ANGGOTA TERHADAP KEBERHASILAN USAHA KUD KARYA SEMBADA DESA BATANG BATINDIH KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Dewi Trisnawati; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This research aims to determine the influence of service and member participation to business success. This research was conducted at KUD Karya Sembada Batang Batindih Village Rumbio Jaya District Kampar Regency with 107 research samples obtained by using simple random sampling method. The data used are primary data and secondary data with data collection methods using questionnaires and documentation. Data analysis techniques used are Descriptive Analysis and Multiple Linear Regression Analysis processed through SPSS 20.0 Program. The results of this research refer to that service and members participation have a significant influence on the business success of cooperative. This means that if the service cooperative be better to members and the cooperative have a better members participation, then the level business success of cooperative will be better too. Thus, to achieve a good level of business success required support from members and cooperative management. Keywords : Service, Member Participation, Business Success